Climate risk and food security in Nepal—analysis of climate impacts on food security and livelihoods - Krishnamurthy, PK; Hobbs, C; Matthiasen, A; Hollema, SR; Choularton, R.J.; Pahari, K; Kawabata, M (2013)
Food security in Nepal is highly sensitive to climate risks. Recent climate-related events, such as the floods of 2008 and the winter drought of 2008/2009, have highlighted the potential impacts of climate on food production, access to markets and income from agricultural activities. However, the ways in which livelihoods and other vulnerabilities are linked to climate have not been well studied. The purpose of this analysis is to quantitatively and qualitatively assess climate (including climate variability, change and extremes) impacts on food security and livelihoods. The analytical method carried out for this research consisted of three components: (i) a dynamic analysis to evaluate the relationship between historic and current climatic variability and food security indicators, using long-term historical data; (ii) a descriptive analysis to establish a baseline against which vulnerability to future risks can be assessed, using household data from the Nepal Living Standards Survey 2010/2011 (NLSS-III); and (iii) a workshop with national stakeholders to validate the results and identify priority adaptation interventions.